2011
DOI: 10.1021/cm201513a
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Fabrication of Colloidal Semiconductor–Metal Hybrid Heterostructures: Site Selective Metal Photo Deposition

Abstract: Reliable synthesis of semiconductor-metal heterostructures would increase their availability for fundamental studies and applications in catalytic, magnetic, and opto-electronic devices. Here, we demonstrate there are three main pathways for the formation of Pt and Pd nanoparticles on CdS and CdS 04 Se 0.6 nanorods. A thermal pathway and photochemical pathway occur when the metal precursor is heated or irradiated directly in the presence of an electron donor, leading to homogeneous nucleation and formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
61
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 52 publications
2
61
0
Order By: Relevance
“…Such localized electrons can then reduce surface-adsorbed Ni 2+ ions, leading to Ni nanoparticle formation. 26,27 A corresponding yellow to greenish color change is observed, indicating Ni NP deposition.…”
Section: Methodsmentioning
confidence: 97%
“…Such localized electrons can then reduce surface-adsorbed Ni 2+ ions, leading to Ni nanoparticle formation. 26,27 A corresponding yellow to greenish color change is observed, indicating Ni NP deposition.…”
Section: Methodsmentioning
confidence: 97%
“…14,15 Using a combined experimental and computational approach, we showed that the time evolution and, formation mechanism and the S-to-Se content of these compositionally graded CdS 1Àx Se x nanorods are direct consequences of relative phosphine chalcogenide precursor reactivity. Further, by tuning the sterics and electronics of a family of closely related R 3 PdE precursors (R = amide, alkyl, aryl or aryloxy; E = S or Se), we reproducibly and predictably synthesized CdE nanorods with controllable aspect (length-todiameter) ratios between 10 and 100.…”
Section: Ialkyl Dichalcogenides (Ràeàeàr;mentioning
confidence: 99%
“…No H 2 and negligible amounts of PhCHO and PhCH 3 were detected for over a week when reactions were carried out in the presence of SC-free, unbound Pt or Pd nanoparticles ( Figure 1b). 29 Photocatalytic experiments were also carried out inside a fancooled Rayonette photoreactor. Unlike the intermittent and cyclical nature of direct sunlight illumination, lamp irradiation provides a constant stream of photons for a more controlled photocatalytic environment.…”
mentioning
confidence: 99%